A collaborative surgical approach to upper and lower abdominal cytoreductive surgery in ovarian cancer. Issue 1 (7th June 2018) - Eng, Oliver S.; Raoof, Mustafa; Blakely, Andrew M.; Yu, Xian; Lee, Stephen J.; Han, Ernest S.; Wakabayashi, Mark T.; Yuh, Bertram; Lee, Byrne; Dellinger, Thanh H.
Abstract : Background and Objectives: Cytoreductive surgery with complete macroscopic resection in patients with ovarian cancer is associated with improved survival. Institutional reports of combined upper and lower abdominal cytoreductive surgery for more advanced disease have described multidisciplinary approaches. We sought to investigate outcomes in patients undergoing cytoreductive surgery in patients with upper and lower abdominal disease at our institution. Methods: Patients who underwent cytoreductive surgery for ovarian malignancies from 2008 to 2015 were retrospectively identified from an institutional database. Upper abdominal cytoreduction was defined anatomically as debulking of disease proximal to the ligament of Treitz. Perioperative outcomes were analyzed. Results: A total of 258 operations were performed, the majority for serous ovarian carcinoma (70%). The gynecologic oncologist was the primary surgeon and often assisted by either a surgical oncology fellow and/or attending. In operations with combined upper and lower abdominal cytoreduction, patients were more likely to have an American society of anesthesiologists physical status classification system (ASA) of 3, peritoneal implants, and liver/spleen metastases. Preoperative chemotherapy and optimal cytoreduction were similar between groups. Perioperative morbidity and mortality were not significantly different between groups. Conclusions: A collaborative surgical approach to combined upper and lower abdominal cytoreductive surgery in patients with ovarian cancer should be performed, if needed, to achieve an optimal cytoreduction.